The Contribution Of Emotional Intelligence In Students' Basketball Playing Skills - Aldilla Aldilla; Nur Saqinah Galugu; Rachmat Hidayat; Imam Pribadi (JUARA : Jurnal Olahraga, 2022)
This research aims to discover the correlation between emotional intelligence and basketball-playing skills in physical education students at the University of Muhammadiyah Palopo. This quantitative research with a correlational design with 29 students who programmed the basketball teaching as the sample. This sample was determined by using the total sampling technique. The Data were collected using an emotional intelligence questionnaire via Google form, while the researcher measured the playing skill using a test. The collected data were analyzed by using SPSS 25.0 for windows. The Correlation test results show that the significant value is smaller than 0.05(0.000 ≤ 0.05), and T- arithmetic is bigger than T-table (5.126≥2.055). Thus, it can be concluded that emotional intelligence correlates with basketball playing skills.